ARTIFICIAL INTELLIGENCE AND LEARNING ANALYTICS IN OPTIMIZING DIGITAL EDUCATION (International Congress on Economics, Management and Business Studies, 2026)
This article explores the role of Artificial Intelligence (AI) and Learning Analytics (LA) in optimizing digital education processes. The study examines how AI tools and data analysis methods allow educators to personalize learning paths, monitor student progress, and improve overall learning outcomes in Informatics and IT education. Results demonstrate that students engaging with AI-driven adaptive exercises and real-time feedback achieve higher retention, enhanced problem-solving skills, and greater engagement. The findings provide practical recommendations for the development of digital education strategies.
Keywords: Artificial Intelligence, Learning Analytics, digital education, adaptive learning, e-learning platforms, personalized learning, IT education, pedagogical technology, student engagement, educational optimization.